Clinical Applications of Remote Ischemic Preconditioning - Kristin Veighey; Raymond J. MacAllister (Cardiology Research and Practice)
Ischemia-reperfusion injury is a composite of damage accumulated during reduced perfusion of an organ or tissue and the additional insult sustained during reperfusion. Such injury occurs in a wide variety of clinically important syndromes, such as ischemic heart disease and stroke, which are responsible for a high degree of morbidity and mortality worldwide. Basic research has identified a number of interventions that stimulate innate resistance of tissues to ischemia-reperfusion injury. Here, we summarise the experimental and clinical trial data underpinning one of these “conditioning” strategies, the phenomenon of remote ischemic preconditioning.